2015
DOI: 10.1016/j.semcdb.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal aspects of Wnt signaling and planar cell polarity during vertebrate embryonic development

Abstract: Wnt signaling pathways act at multiple locations and developmental stages to specify cell fate and polarity in vertebrate embryos. A long-standing question is how the same molecular machinery can be reused to produce different outcomes. The canonical Wnt/β-catenin branch modulates target gene transcription to specify cell fates along the dorsoventral and anteroposterior embryonic axes. By contrast, the Wnt/planar cell polarity (PCP) branch is responsible for cell polarization along main body axes, which coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 159 publications
0
57
0
Order By: Relevance
“…In vertebrates, the Fz-PCP pathway has also been shown to control coordinated cellular behaviours within mesenchymal tissues. Examples include cell intercalation during gastrulation, cell orientation in the developing limb bud, and cell-to-cell interactions within migratory neural crest streams (Goodrich and Strutt, 2011;Gao and Yang, 2013;Mayor and Theveneau, 2014;Sokol, 2015). As there are vertebral defects in both Fz-PCP and the Fat4 and Dchs1 mutants, we considered the possibility that Fat4-Dchs1 might regulate polarised cell behaviours and rearrangements during sclerotomal morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In vertebrates, the Fz-PCP pathway has also been shown to control coordinated cellular behaviours within mesenchymal tissues. Examples include cell intercalation during gastrulation, cell orientation in the developing limb bud, and cell-to-cell interactions within migratory neural crest streams (Goodrich and Strutt, 2011;Gao and Yang, 2013;Mayor and Theveneau, 2014;Sokol, 2015). As there are vertebral defects in both Fz-PCP and the Fat4 and Dchs1 mutants, we considered the possibility that Fat4-Dchs1 might regulate polarised cell behaviours and rearrangements during sclerotomal morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The two best characterised ones are the so-called canonical pathway, which regulates target gene expression, and the non-canonical planar cell polarity pathway (Sokol, 2015). Here we focus on canonical signalling, which is initiated by the binding of Wnt to a member of the Frizzled family of serpentine receptors and the coreceptor LRP5/6 (MacDonald and He, 2012).…”
mentioning
confidence: 99%
“…We compared different concentrations of gelatin and found that 0.5% gelatin in DMEM significantly increased the proliferation of Ad-MSCs, possibly via activation of the canonical pathway for wnt signaling. The activation of wnt/catenin pathways leads to increased cell proliferation during embryonic development (Sokol, 2015). This also regulates cell proliferation in certain mammalian tissues, which are in a state of constant regeneration (Clevers et al, 2014).…”
Section: Discussionmentioning
confidence: 99%